Big snowman, little snowman - Rabe, Tish; Disney Storybook Artists (New York : Random House, 2013)
When a prophecy traps a kingdom in eternal winter, Princess Anna teams up with Kristoff and his reindeer to embark on a journey to find Anna's sister, the Snow Queen Elsa, to put an end to her icy spell.
At head of title: Disney Frozen.
310
Accelerated Reader
Keywords: Princesses -- Fiction; Reindeer -- Fiction; Stories in rhyme; Princesses -- Fiction; Reindeer -- Fiction; Stories in rhyme